The Influence Process of Science Skill and Motivation Learning with Creativity Learn - Yoga Budi Bhakti; Irnin Agustina Dwi Astuti (Journal of Education and Learning (EduLearn), 2018)
This research aims to understand the influence process of science skill and motivation learning with creativity learn. Data about the process of scince skill, motivation and creativity learn collected by test questioner instrument. Data analysis with regression analysis and correlation. Research shows that: There is the influence of skill process of science to the process of creativity learn with correlation coefficient r=0.634, there is the influence of motivation learn students to creativity learning with correlation coefficient r=0.55, the process of science skills and motivation to study for students influence of creativity learn with correlation coefficient r=0.935. This study concluded that skill process of science and the motivation to study student could creative learning.